Penerapan Data Mining Untuk Memprediksi Kompetensi Siswa Menggunakan Metode Decission Tree ( Studi Kasus SMK Multicomp Depok ) - Rizmayanti, Ade Irma; Hidayati, Nadiyah; Nugraha, Fitra Septia; Gata, Windu (Swabumi, 2021)
Abstract- This study discusses the application of data mining to predict student competencies using the decision tree method. In this study applying data mining to predict student competency using the decision tree method. This research was conducted to predict student learning outcomes based on report card grades semester 1, semester 2 semester 3 and semester 4. Data were then managed using Rapid Miner to facilitate predicting student competencies. The study was conducted at Multicomp SMK which has 3 majors namely Hospitality Accommodation, Online Business and Marketing and Multimedia. Research using data from students in each department includes class X and class XI. The application of data mining is used to predict student competencies by using a decision tree and C 4.5 algorithm as a support as well as a comparison to determine the competency of students of Multicomp Depok Vocational School based on both methods. This method is able to measure the ability of students appropriately and be able to provide an understanding at a certain level according to the needs of Indonesian education has a pattern and learning strategy based on students' reasoning abilities. Students are expected to be able to analyze a problem well and find the right solution. students are not accompanied by an adequate education system or curriculum. Teacher competencies that are not evenly distributed in various schools and governments are felt to be very lacking in realizing reasoning based education systems.